Surface impedance of copper MOB depending on the annealing temperature and deformation degree - Kutovoj, V.A.; Nikolaenko, A.A.; Stoev, P.I.; Vinogradov, D.V. (Вопросы атомной науки и техники, 2006)
Results of researches of influence of annealing temperature and deformation degree on mechanical features of
copper MOB are presented. It is shown that minimal surface resistance is observed in copper samples that were subject
to pre-deformation and were annealed in the range of temperatures 873…923K. Представлены результаты исследований влияния температуры отжига и степени деформации на электромеханические характеристики меди марки МОБ. Показано, что минимальное поверхностное сопротивление наблюдается у меди, деформированной и отожженной в интервале температур 873…923К. Представлені результати досліджень впливу температури відпалу та степені деформації на
електромеханічні характеристики міді марки МОБ. Показано, що мінімальний поверхневий опір
спостерігається у зразків міді, підверненої деформації і відпаленої в інтервалі температур 873…923К.